Development of Student Worksheet Based on Learning Cycle 5E on Stoichiometry Material - Lydra, Iqbal Abdan; Mawarnis, Elvy Rahmi; Herman, Mimi (Hydrogen: Jurnal Kependidikan Kimia, 2023)
This study addresses the insufficiency of teaching materials in the learning process and its negative impact on students’ comprehension of provided material. To alleviate this issue, student worksheets based on Learning Cycle 5E were developed to be used as a learning resource for 10th-grade students studying stoichiometry at State Senior High School (SMAN) 1 X Koto Singkarak. The aim of this research was to create a valid and practical Student worksheet based on Learning Cycle 5E. Development research with the 4-D development model (define, design, development, and disseminate) was employed, with the first three stages executed. The define stage was conducted to identify the school’s conditions and problems, while the design stage was used to create the initial student worksheet based on Learning Cycle 5E for stoichiometry material. The develop stage was carried out to refine the worksheet. Data were gathered using validation sheets and practicality questionnaires filled out by two chemistry lecturers, one chemistry teacher, and 10th-grade students of SMAN 1 X Koto Singkarak. Data analysis was conducted using a quantitative descriptive method. Results indicated that the Student worksheet based on Learning Cycle 5E met the valid criteria with a validation score of 91.37% and the practical criteria with a student response questionnaire score of 82.09%. Thus, the worksheet can be used as a learning resource.